The South Caucasus and Iran in the post-sanctions era: Pursuing greater interconnectedness amidst continuing constraints and scaled-down expectations - Andrea Weiss; Yana Zabanova (Stiftung Wissenschaft und Politik (SWP), 2017)
The lifting of international nuclear-related sanctions on Iran in January 2016 was enthusiastically welcomed by the Islamic Republic's neighbours in the South Caucasus. Armenia, Azerbaijan, and Georgia have hoped that Iran's rapprochement with the West and the unfreezing of some hundred billion dollars worth of assets abroad would lead Iran to step up its trade and investment activities in the Caucasus, especially in the energy and transport sectors. However, the anticipated benefits have been slow in coming, as Iran has shown reluctance to fund infrastructural projects in the Caucasus. On the other hand, there have been positive developments in trade and tourism flows and the power transmission sector. On the whole, although Iran is interested in closer economic cooperation with the South Caucasus, it relies on the region's countries to provide the momentum and secure the resources necessary to achieve this goal.
Keywords: 320